Excess shear stress analysis of complex geological structures in underground mines - Hofmann, G.F. (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
Shear deformation on weak geological structures, such as shear zones, faults or orebody contacts, can pose a significant seismic hazard in underground mines. The mine geological model can be complex, and when the whole underground mine is considered by elastic numerical modelling, the dataset can be large and challenging to manage using commercially available modelling software. A procedure has been developed to use the triangulation defining the geometrical models of structures directly, not requiring any surface fitting or simplification. The polygon orientations and stress tensors from boundary element numerical modelling, are used to calculate the normal and shear stress components at the centroid of each polygon, from which excess shear stress is derived as a failure criterion for structure-related seismic hazard. The proposed procedure enables visualisation of modelled excess shear stress for the full geological model, highlighting areas of potential co-seismic shear deformation along structures. It is also useful to quantify and visualise the modelled seismic hazard relative to mine tunnels, since this is where mine workers are exposed. A statistical approach is used to derive consistent, quantified overstressing values accounting for possible unrealistic results from elastic modelling. The methodology is described in a case study for a sublevel stoping mine, currently at a depth of 1,000 m. The geological model is large and complex, and it is a challenge to analyse and represent structure-related seismic hazard. The historical conditions were used to derive and verify modelling criteria, which were then used to simulate expected conditions to 2,000 m below surface. The methodology was used to assess the seismic hazard by identifying the potential for large events and tunnels vulnerable to damaging ground motions.